Factors Affecting Students’ Motivation on Learning in Higher Education - Pandey, Shiv Ram; Acharya, Ajit; Subedi, Abha (KMC Research Journal, 2025)
This review article explores on the factors that motivate and demotivate students’ learning. It analyzes how students are motivated towards learning, and why they are not motivated in their learning with detail exploration on the role of relevant stakeholders towards students’ motivation. The available literature shows that motivation comes from different sources such as physiological needs, social needs, self-esteem needs, teachers’ behaviour, parents’ dealing, educational leaders, peer effects, curriculum, policy and resources. The study is based on secondary sources of data. Books, journals, theses and documents related to students’ motivation were reviewed to stand strong conceptually and theoretically. The study explored that student, teacher, administration, environment and policy related factors affect much on students’ motivation in higher education.